Function-led innovation kit framework for occupational therapy creative activities process in Malaysia - Mat Yusof, Nurhikma (2022)
Creative activities in rehabilitation setting especially in occupational therapy (OT) posits innovative adaptive tool (AT) used as a bridge to client’s recovery during assessment and exercise. Creation covers from pediatric rehabilitation, cancer rehabilitation, musculoskeletal rehabilitation, psychosocial rehabilitation, geriatric rehabilitation, and pulmonary and cardiac rehabilitation. However, reported several reasons for non-use which include device failure (broken or non-functioning devices), incorrect prescription or fit with individual need, lack of appropriate instruction, feelings of embarrassment or awkwardness in device use, poor aesthetic quality, and denial of need or embarrassment over disability. Therefore, the main objective of the study is to enhance understanding among therapist as the expert user in rehabilitation setting on creative process; perhaps to facilitate better adaptive tool towards client’s recovery by implementing design practice into their creation process. Mix-method exploratory sequential design were implemented with two instruments used to collect data which started with semi-structured interview and a questionnaire-based survey. Six experts from design and rehabilitation were interviewed to identify the adaptation creation attributes and followed by forty-two therapist’s feedback on the survey based on their adaptation experience using design practice to support the findings. As a result, six adaptation attributes were identified via interview and validated through survey and an adaptation design framework for occupational therapy creative activities was developed. In future, results from this study will explore relevancies of design practice in other field especially for the expert user and are expected to lead new design approach to expert user in their creation activities. This will create awareness of good design and stimulus importance role of design and designer in the future.